2022
DOI: 10.3390/tropicalmed7080152
|View full text |Cite
|
Sign up to set email alerts
|

Drugs for Intermittent Preventive Treatment of Malaria in Pregnancy: Current Knowledge and Way Forward

Abstract: Malaria infection during pregnancy is an important driver of maternal and neonatal health in endemic countries. Intermittent preventive treatment in pregnancy (IPTp) with sulfadoxine-pyrimethamine (SP) is recommended for malaria prevention at each scheduled antenatal care visit, starting at the second trimester, in areas of high and moderate transmission. However, the increased resistance to SP in some endemic areas challenges its effectiveness. Furthermore, SP is contraindicated in the first trimester of preg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 105 publications
0
5
0
Order By: Relevance
“…Revisiting existing drugs with safe clinical use is an alternative to the development of new molecules. In vitro studies have shown that mefloquine, a well-known molecule widely used in the treatment of malaria [ 209 ], acts as an efflux pump inhibitor in P. aeruginosa [ 210 ]. Trimethoprim, a drug used in combination with sulfamethoxazole to treat various infections, also has efflux pump inhibitory activity.…”
Section: Efflux Pumps As Targets For New Drugsmentioning
confidence: 99%
“…Revisiting existing drugs with safe clinical use is an alternative to the development of new molecules. In vitro studies have shown that mefloquine, a well-known molecule widely used in the treatment of malaria [ 209 ], acts as an efflux pump inhibitor in P. aeruginosa [ 210 ]. Trimethoprim, a drug used in combination with sulfamethoxazole to treat various infections, also has efflux pump inhibitory activity.…”
Section: Efflux Pumps As Targets For New Drugsmentioning
confidence: 99%
“…For example, the total molecular weight, cLogP (octanol/water coefficient, solubility estimation), and the number of sp3 atoms (stereochemical complex-ity estimation) were calculated and statistically analyzed (Table S2). The results suggest that 3-nitroimidazopyridines derivatives (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24), metronidazole hybridized derivatives , and quinoline-metronidazole derivatives (63a-63m) have high molecular weights compared with other 5-NI derivatives. These kinds of compounds are in the upper recommended limit to be considered "drug-like" compounds, according to the empirical rules proposed by Lipinsky [70].…”
Section: Discussionmentioning
confidence: 94%
“…Currently, drugs used as malaria treatment are divided into four categories (Figure 3): quinolines or aminoquinolines (e.g., chloroquine and primaquine); antifolates (e.g., sulfadoxine and pyrimethamine); artemisinin derivatives; and macrocycles, such as tetracycline and doxycycline [11]. However, although there are different types of drugs and novel poly-drug therapies, a growing concern is the emergence of drug-resistant Plasmodium strains [10,12].…”
Section: -Nitroimidazole Derivatives With Antimalarial Activitymentioning
confidence: 99%
“…33 Chloroquine was not well tolerated in pregnancy trials nor were attempts at substituting SP with mefloquine, amodiaquine or azithromycin. [34][35][36] IPTp with dihydroartemisin-piperaquine (DP) is the most promising alternative to IpTP-SP perhaps because of the long half-life of piperaquine that may serve as prophylaxis against future mosquito bites as well as clearing any parasites sequestered in the placenta at the time of administration. Compared with IPTp-SP, IPTp-DP was associated with a lower risk of clinical malaria, peripheral parasitemia during pregnancy, and placental malaria at delivery.…”
Section: Chemoprophylaxismentioning
confidence: 99%
“…SP resistance has led researchers to evaluate alternative antimalarials for chemoprophylaxis in pregnancy, including the reintroduction of chloroquine, an early antimalarial with widespread resistance whose efficacy in Africa reappeared after years of not recommending its use 33 . Chloroquine was not well tolerated in pregnancy trials nor were attempts at substituting SP with mefloquine, amodiaquine or azithromycin 34–36 . IPTp with dihydroartemisin-piperaquine (DP) is the most promising alternative to IpTP-SP perhaps because of the long half-life of piperaquine that may serve as prophylaxis against future mosquito bites as well as clearing any parasites sequestered in the placenta at the time of administration.…”
Section: Prevention Of Malaria In Pregnancymentioning
confidence: 99%